THE EFFECTS OF FUSEL OIL BLENDING ON GASOLINE FUEL CHARACTERISTICS - E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1987)
Fusel oil, which comprises a mixture of kigher alcohols, has prospective potentialirien for use at a conobrent in gasoline-methanol blends since ir can improve their water tolerance, Thie has been demonatrated in an earlier work by the author. The present paper presents the reults of a serier of tests made to investigate the effects of funel oil addition to the actual gasoline fuel characterisies The resules indicated that such addition Could remult in improving the gsoline propertles s can be exemined through comparisom with the established specifications.